Total energy expenditure assessment in elite junior basketball players: A validation study using doubly labeled water - Silva, A. M.; Santos, D. A.; Matias, C. N.; Minderico, C. S.; Schoeller, D. A.; Sardinha, L. B. (The Journal of Strength and Conditioning Research, 2013)
An accurate assessment of total energy expenditure (TEE) during a competitive season is required. We aimed to validate TEE estimated by self-reported energy intake (EI) and the dietary reference intake (DRI) method in 19 elite basketball players (aged 16-18 years) using doubly labeled water (DLW) as the reference method. The DRI models and EI from dietary records over a 7-day period were simultaneously assessed for TEE estimation. Resting energy expenditure was assessed by indirect calorimetry. Fat and fat-free mass (FFM) were determined by a 4-compartment model (body volume by air displacement plethysmography, bone mineral by DXA, and water by deuterium dilution). Fat and FFM ranged from 4 to 19 kg and from 47 to 81 kg, respectively. The physical activity level ranged from 2.2 to 3.7 with a mean value of 2.8 ± 0.4. Total energy expenditure from DLW (17,598 ± 3,298 kJ/d) was significantly underestimated by EI (11,274 ± 2,567 kJ/d), whereas no differences were found using DRI (17,008 ± 3,206 kJ/d). The EI and DRI methods explained TEE from DLW by 34% (p = 0.057) and 44% (p = 0.002), respectively, and wide limits of agreement were observed. Our findings suggested that EI is not a valid tool for TEE assessment. The DRI method may be valid at a group level but inaccurate for estimating individual TEE in young players during a demanding competitive season period.